2RXS—The deepest and cleanest X‐ray all‐sky catalogue before eROSITA1. Issue 9 (24th November 2017) - Boller, Th.
Abstract : We have updated and improved the source catalog obtained from the ROSAT all‐sky survey. In this new version of the source catalog (Second ROSAT all‐sky survey, 2RXS), we have made a number of improvements, paying particular care to reduce spurious sources. The final catalog contains about 135, 000 X‐ray sources, thereby providing the deepest and cleanest all‐sky survey to date. For each source, new data products, including spectra and light curves, were created, allowing to take full advantage of this catalog for new scientific explorations.